2018
DOI: 10.1590/1983-1447.2018.2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Prurido no paciente em hemodiálise: associação com ingestão de fósforo e nível sérico de cálcio

Abstract: Resumo OBJETIVO Analisar a associação entre a ocorrência do prurido e a adesão à dieta prescrita, indicadores bioquímicos da função renal e a qualidade da hemodiálise, em pacientes renais crônicos. MÉTODO Estudo transversal, realizado em uma clínica de diálise no Nordeste do Brasil, com 200 pacientes submetidos à hemodiálise, no primeiro semestre de 2015. Para análise dos dados fez-se uso da estatística inferencial, através dos testes de Qui-Quadrado e Exato de Fisher; e teste de U de Mann Whitney. RESULTAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
(17 reference statements)
0
8
0
1
Order By: Relevance
“…Cutaneous manifestation frequently associated with end-stage renal disease is pruritus, and this symptom results in significant changes in the quality of life of the sufferer, sleep disturbances, and depression potentiating the risk of morbidity [3]. The majority of patients belonged to an age range of 50-61 years [2,3,5,10,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cutaneous manifestation frequently associated with end-stage renal disease is pruritus, and this symptom results in significant changes in the quality of life of the sufferer, sleep disturbances, and depression potentiating the risk of morbidity [3]. The majority of patients belonged to an age range of 50-61 years [2,3,5,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous manifestation frequently associated with end-stage renal disease is pruritus, and this symptom results in significant changes in the quality of life of the sufferer, sleep disturbances, and depression potentiating the risk of morbidity [3]. The majority of patients belonged to an age range of 50-61 years [2,3,5,10,11]. No gender discrimination was observed in the development of pruritus among patients of CKD in multiple studies [3,5,11,12], while a few studies reported increased prevalence in the male gender [2,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Terms like "Skin" and "Abdomen" are linked to people with chronic kidney disease, because these are locations where they show physical changes, which requires attention from the health team must during clinical assessment. For example, the occurrence of pruritus in the skin can be a consequence of the accumulation of uremic substances, elevated serum levels of calcium and phosphorus and secondary hyperparathyroidism (32) . The abdomen, on the other hand, may be a location that shows signs and symptoms of changes in the disease originated, for example, by nutritional intake.…”
Section: Discussionmentioning
confidence: 99%